Effects Induced by Osteophytes on the Strain Distribution in the Vertebral Body Under Different Loading Configurations - Marras, Daniele; Palanca, Marco; Cristofolini, Luca (Frontiers in Bioengineering and Biotechnology, 2021)
The mechanical consequences of osteophytes are not completely clear. We aimed to understand whether and how the presence of an osteophyte perturbs the strain distribution in the neighboring bone. The scope of the study was to evaluate the mechanical behavior induced by the osteophytes using full-field surface strain analysis in different loading configurations. Eight thoracolumbar segments, containing of a vertebra with an osteophyte and an adjacent vertebra without osteophyte (control), were harvested from six human spines. The position and size of osteophytes were evaluated from clinical Computed Tomography images. The spine segments were biomechanically tested in the elastic regime in different loading configurations while the strains over the frontal and lateral surface of vertebral bodies were measured with Digital Image Correlation. The strain fields in the vertebrae with and without osteophytes were compared. The correlation between osteophyte size and strain alteration was explored. The strain fields measured in the vertebrae with osteophytes were different from the control ones. In pure compression, we observed a mild trend between the size of the osteophyte and the strain distributions (R2 = 0.32, p=0.15). A slightly stronger trend was found for bending (R2 = 0.44, p=0.075). This study suggests that the osteophytes visibly perturb the strain field in the nearby vertebral area. However, the effect on the surrounding bone is not consistent: indeed, in some cases the osteophyte shielded the neighboring bone, in other cases the osteophyte increased the strains.